Cancer Risk Following HLA-Incompatible Living Donor Kidney Transplantation - Jennifer D. Motter, MHS; Allan B. Massie, PhD; Jacqueline M. Garonzik-Wang, MD, PhD; Ruth M. Pfeiffer, PhD; Kelly J. Yu, PhD; Dorry L. Segev, MD, PhD; Eric A. Engels, MD, MPH (Transplantation Direct, 2023)
Background. Incompatible living donor kidney transplant recipients (ILDKTr) require desensitization to facilitate transplantation, and this substantial upfront immunosuppression may result in serious complications, including cancer. Methods. To characterize cancer risk in ILDKTr, we evaluated 858 ILDKTr and 12 239 compatible living donor kidney transplant recipients (CLDKTr) from a multicenter cohort with linkage to the US transplant registry and 33 cancer registries (1997–2016). Cancer incidence was compared using weighted Cox regression. Results. Among ILDKTr, the median follow-up time was 6.7 y (maximum 16.1 y) for invasive cancers (ascertained via cancer registry linkage) and 5.0 y (maximum 16.1 y) for basal and squamous cell carcinomas (ascertained via the transplant registry and censored for transplant center loss to follow-up). Invasive cancers occurred in 53 ILDKTr (6.2%) and 811 CLDKTr (6.6%; weighted hazard ratio [wHR] 1.01; 95% confidence interval [CI], 0.76-1.35). Basal and squamous cell carcinomas occurred in 41 ILDKTr (4.8%) and 737 CLDKTr (6.0%) (wHR 0.99; 95% CI, 0.69-1.40). Cancer risk did not vary according to donor-specific antibody strength, and in an exploratory analysis, was similar between CLDKTr and ILDKTr for most cancer types and according to cancer stage, except ILDKTr had a suggestively increased risk of colorectal cancer (wHR 3.27; 95% CI, 1.23-8.71); however, this elevation was not significant after correction for multiple comparisons. Conclusions. These findings indicate that the risk of cancer is not increased for ILDKTr compared with CLDKTr. The possible elevation in colorectal cancer risk is unexplained and might suggest a need for tailored screening or prevention.